2012
DOI: 10.3390/ijms14010057
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Specific DNA Repeats: Rapid Identification in Silico and Validation Using Fluorescence in Situ Hybridization

Abstract: Chromosome enumeration in interphase and metaphase cells using fluorescence in situ hybridization (FISH) is an established procedure for the rapid and accurate cytogenetic analysis of cell nuclei and polar bodies, the unambiguous gender determination, as well as the definition of tumor-specific signatures. Present bottlenecks in the procedure are a limited number of commercial, non-isotopically labeled probes that can be combined in multiplex FISH assays and the relatively high price and effort to develop addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…During preparation of this manuscript, Ioannou et al demonstrated this, using BAC clones from Roswell Park Cancer Institute RP11 library. We decided to combine preexisting DNA repeat probes with optimized BAC contigs, which were identified using bioinformatics 22,42 to obtain optimal specificity and brightness (Table 2). Now, combining the versatility of BACs and preexisting repeat probes with a wide repertoire of different fluorochromes, together with the use of the SKY system, resulted in a cost-effective, flexible, and reliable methodology to detect four sets of six probes in interphase nuclei (see Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During preparation of this manuscript, Ioannou et al demonstrated this, using BAC clones from Roswell Park Cancer Institute RP11 library. We decided to combine preexisting DNA repeat probes with optimized BAC contigs, which were identified using bioinformatics 22,42 to obtain optimal specificity and brightness (Table 2). Now, combining the versatility of BACs and preexisting repeat probes with a wide repertoire of different fluorochromes, together with the use of the SKY system, resulted in a cost-effective, flexible, and reliable methodology to detect four sets of six probes in interphase nuclei (see Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the coverage of all the chromosomes and devising sophisticated, fast, and reliable methods to evaluate these single cells is favorable as not all of the possible numerical abnormalities can be currently assessed due to the limited number of available chromosome-specific probes and the limited number of suitable fluorochromes. 21,22 Here, we present the selection of human probe DNA and a technique using multistep FISH employing four sets of six labeled FISH probes able to delineate all 24 human chromosomes in interphase cells. This full karyotype analysis approach will provide additional diagnostic potential for single-cell analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A2780 cell line (broadly defined as epithelial ovarian cancer to include, serous, clear cell and endometriod cancer) was obtained from ATCC (VA, USA). All cell lines were verified via short tandem repeat analysis [21]. Cell lines were maintained in RPMI-1640 (Life Technologies Cooperation, NY, USA) supplemented with 10% FBS, 1% L-glutamine.…”
Section: Methodsmentioning
confidence: 99%
“…We chose to search the genome database at UC Santa Cruz [ 45 ], which shows alignments of paired end-sequenced bacterial artificial chromosome clones (BACs) [ 46 , 47 ] with the provisionally finished draft of the human genome sequence [ 48 ]. In our most recent approach to prepare high performance DNA probes that supersede preexisting probes with regard to probe specificity and signal-to-noise ratios, we attempt to identify BAC clones from the pericentromeric regions of different chromosomes that are free of non-chromosome-specific short or long interspersed repeat sequences (SINE’s, LINE’s) and contain ‘pure’ satellite DNA ( Figure 1 ) [ 49 51 ].…”
Section: Mini Reviewmentioning
confidence: 99%
“…As the example in Figure 1 illustrates, the alignment of paired end-sequences from BAC clone RP11-416F8 suggests an insert of about 26.678 kb of human DNA mapping to chromosome 16, band q11.2 [ 51 ]. The insert is predicted to be comprised entirely of satellite DNA.…”
Section: Mini Reviewmentioning
confidence: 99%